Immunological characteristics of bronchoalveolar lavage fluid and blood across connective tissue disease-associated interstitial lung diseases - Hirano, Aiko; Sakashita, Aki; Fujii, Wataru; Baßler, Kevin; Tsuji, Taisuke; Kadoya, Masatoshi; Omoto, Atsushi; Hiraoka, Noriya; Imabayashi, Tatsuya; Kaneko, Yoshiko; Sofue, Hideaki; Maehara, Yosuke; et al. (Frontiers in Immunology, 2024)
Interstitial lung disease (ILD) is a serious complication of connective tissue diseases (CTDs). The heterogeneity of ILDs reflects differences in pathogenesis among diseases. This study aimed to clarify the characteristics of CTD-ILDs via a detailed analysis of the bronchoalveolar lavage fluid (BALF) and blood immune cells. BALF and blood samples were collected from 39 Japanese patients with newly diagnosed ILD: five patients with Sjögren’s syndrome (SS), eight patients with dermatomyositis (DM), six patients with rheumatoid arthritis (RA), six patients with systemic sclerosis, four patients with anti-neutrophil cytoplasmic antibody-associated vasculitis, and 10 patients with idiopathic interstitial pneumonia. We performed single-cell RNA sequencing to analyze the gene expression profiles in these patients’ immune cells. In patients with SS, B cells in the BALF were increased and genes associated with the innate and acquired immunity were enriched in both the BALF and blood. In contrast, patients with DM showed an upregulation of genes associated with viral infection in both the BALF and blood. In patients with RA, neutrophils in the BALF tended to increase, and their gene expression patterns changed towards inflammation. These disease-specific characteristics may help us understand the pathogenesis for each disease and discover potential biomarkers.